A descriptive study to analyze chemotherapy-induced hair loss and its psychosocial impact in adults: Our experience from a tertiary care hospital - Neerja Saraswat; Ajay Chopra; Aradhana Sood; Parul Kamboj; Sushil Kumar (Wolters Kluwer Medknow Publications, 2019)
Background: Hair loss is one of the most commonly reported and psychologically distressing adverse effects of chemotherapeutic agents. Studies on its impact on psychosocial aspect of cancer patients are lacking at present. Objective: To study the chemotherapeutic agents causing hair loss and its psychosocial implications in adults. Materials and Methods: Observational study was done for a period of 1 year, wherein all cancer patients, more than 18 years of age who developed hair loss while on chemotherapy were assessed for type of malignancy, details of chemotherapy protocol, their knowledge about chemotherapeutic agents induced hair loss, and its impact on their social life and patterns of adjustment to deal with it. A prevalidated closed-ended questionnaire was used as a data collection tool. Results: Out of 179 patients, 96 (53.6%) were males as against 80 (44.6%) females, and 49 (27.3%) patients were between 18 and 30 years of age. Carcinoma lung was the most common malignancy seen in 46 (25.6%) patients followed by rectosigmoid carcinoma in 41 (22.9%) patients. Combination of cyclophosphamide and doxorubicin was the most common combination resulting in hair loss in 49 (27.3%) cancer patients. A total of 101 (56.4%) patients felt that hair loss was the worst side effect of chemotherapy, while 29 (16.2%) had to continue because it was life-saving. A total of 129 (72%) patients said hair loss is affecting their social life; 37 (20.6%) patients were using hair accessories while 69 (38.5%) did not even attempt to hide hair loss as they were too occupied with fear of disease. Conclusion: Chemotherapy-induced hair loss is a common adverse effect in cancer patients undergoing treatment. A thorough counseling about it and methods to deal with it should be a part of management of the patients.